2020
DOI: 10.1021/acsanm.9b02576
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Control-Enabled Enhancement in Hydrophilicity and Mechanical Toughness in Nanocrystalline Tungsten Oxide Films for Energy-Related Applications

Abstract: We report on the phase-control-enabled enhancement in the hydrophilicity and mechanical properties of nanostructured WO3 films for energy-related applications. Nanostructured WO3 films were fabricated by utilizing reactive magnetron sputter deposition onto silicon (100) substrates with varying deposition temperature (T s = 25–500 °C) at a fixed oxygen partial pressure of ∼4 mTorr. Extensive characterization performed indicates that the fundamental surface/interface structure–phase–hydrophilicity–mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 62 publications
(189 reference statements)
0
6
0
Order By: Relevance
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/polym14122492/s1, Figure S1: Representative advancing (θa) and receding (θr) water contact angles of the membranes; Table S1: Reported (static) water contact angles of different WO 3 layers. References [75][76][77][78][79][80][81][82][83][84][85][86][87] are cited in the supplementary materials. Funding: This research was funded by Project no.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/polym14122492/s1, Figure S1: Representative advancing (θa) and receding (θr) water contact angles of the membranes; Table S1: Reported (static) water contact angles of different WO 3 layers. References [75][76][77][78][79][80][81][82][83][84][85][86][87] are cited in the supplementary materials. Funding: This research was funded by Project no.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“… 24 , 28 , 35 , 40 44 However, the catalytic studies on the hard magnetic materials such as barium- and strontium-hexaferrites and their derivatives are yet to be explored. On the other hand, based on our previous work on magnetic and electronic materials, 45 , 46 we recognize that tailoring the materials’ structure and controlled phase in nanostructured materials can provide opportunities to design inexpensive nanomaterials for the desired applications. Furthermore, most recently, we demonstrated that the surface/interface magnetic properties can be tailored 46 and have made successful attempts to derive catalytic properties in Cu-substituted strontium hexaferrites synthesized using a tartrate-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, conversion of nitrophenol into other chemicals such as para -aminophenol is highly beneficial as these chemicals can be used as starting materials for industrial dyes, photography development agents, rubber chemicals, and so forth. , While there are recent attempts to design and develop catalysts for the purpose based on environmental friendly, cost-effective, and high-performance materials, catalysts based on noble metals, such as Au, Pd, Pt, Ag, and so forth, have been studied for a long time to convert para -nitrophenol to para -aminophenol. ,, Realizing that the noble metals are expensive, which exhibit sintering and related problems at the nanoscale dimensions, many researchers directed their recent efforts to design and develop various other catalysts, which are based on inexpensive, green, and highly stable metal oxides and/or composites, for the para -nitrophenol reduction reaction. ,,, However, the catalytic studies on the hard magnetic materials such as barium- and strontium-hexaferrites and their derivatives are yet to be explored. On the other hand, based on our previous work on magnetic and electronic materials, , we recognize that tailoring the materials’ structure and controlled phase in nanostructured materials can provide opportunities to design inexpensive nanomaterials for the desired applications. Furthermore, most recently, we demonstrated that the surface/interface magnetic properties can be tailored and have made successful attempts to derive catalytic properties in Cu-substituted strontium hexaferrites synthesized using a tartrate-gel method. , Therefore, in the present study, Al is chosen for the substitution in place of Fe in SrFe 12 O 19 and evaluated its activity toward the nitrophenol reduction reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Today’s world is increasingly shaped by information technology and the need for advanced materials with enhanced properties and performance is ubiquitous in the current scenario [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The technical advancements in the recent years have paved way for miniaturization of electronic, magnetic, and optoelectronic devices with high performance, which is fundamentally dependent on the physical, chemical, and electromagnetic properties of their respective electronic, optical, magnetic, and electromagnetic components [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is important since it gives a clear understanding of the underlying mechanisms that governs the properties that are of direct relevance for the desired technological application. In most applications, electrically conducting or mechanically protective materials used are in the form of thin films, where improved efficiency and cost effectiveness is important [ 6 ].…”
Section: Introductionmentioning
confidence: 99%